"Journal: 100 Years / Mining & Scientific Press San Francisco April 10, 1909 / Methods of Testing Electric Detonators" - William Nicoll (International Society of Explosives Engineers, 2010)
Those who use electric detonators in firing blasts will be interested in a new electrical testing instrument known as the ‘Blasters’ Friend’, recently devised by the New York Blasting Supply Co. of New York. Owing to the necessarily delicate construction of the platinum wire bridge in the shell of a detonator, it frequently happens that it becomes broken or disconnected; thus destroying the circuit and rendering the detonator worthless. In many cases, misfires and premature explosions are caused by defective detonators. Heretofore, to detect the deficiencies of a detonator before using has been an impossibility, owing to the absence of a testing instrument adapted to the purpose.